Influence of agitation and solvent percentage on the extraction of phytochemical compound from Asystasia gangetica - Norazwina, Zainol; Nor Hazwani, Aziz; Amir Syarifudin, Baharudin (Elsevier Ltd, 2023)
This study aims to investigate the influence of agitation and solvent percentage on the phytochemical extraction from Asystasia gangetica through response surface methodology and to optimize the extraction condition. The experiment was conducted based on the central composite design with two variables: solvent percentage and agitation speed. The total phenolic compound (Folin–Ciocalteu method), total flavonoid compound (Dowd method), and antioxidant activity (modified DPPH free radical scavenging assay), were analyzed through the analysis of variance. All models were significant (p-value <0.05) with strong R2 values (over 80 %), indicating satisfactory regression analysis. The optimum condition is achieved at 204 rpm agitation speed and 72 % solvent percentage with total phenolic, total flavonoid, and antioxidant activity at its maximum value of 0.2086 mg/ml, 0.2082 mg/ml, and 1.0494 nmol/ul, respectively. The influence of factors on each phytochemical varies, with both being significant for total flavonoid compound extraction and insignificant for antioxidant activity. Meanwhile, for the total phenolic compound, the solvent percentage is insignificant. Determining the significant factors during phytochemical extraction could be useful in tailoring the suitable range to maximize yield. The bioactive compounds and nutritional composition of A. gangetica could be used to develop functional foods and development of drugs to manage various disease.